- #1

A_Munk3y

- 72

- 0

## Homework Statement

derive f(x)=x

^{2}+2x+1/ x

^{2}-3x+2

## The Attempt at a Solution

(x

^{2}-3x+2)(d/dx)(x

^{2}+2x+1)-(x

^{2}+2x+1)(d/dx)(x

^{2}-3x+2)/(x

^{2}-3x+2)

^{2}

=(x

^{2}-3x+2)(2x+2)-(x

^{2}+2x+1)(2x-3)

=(2x

^{3}-4x

^{2}-2x+4)-(2x

^{3}+x

^{2}-4x-3)

=5x

^{2}+2x+7/(x

^{2}-3x+2)

^{2}

that's what I'm getting... but according to the online derivative calculator, it's 5x

^{2}-2x-7/(x

^{2}-3x+2)

^{2}

what am i doing wrong? i keep checking the simplification and i keep getting the same answer